1956
DOI: 10.1002/recl.19560750505
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of n‐alkanes

Abstract: The properties of the crystalline Sg-modifications of n-alkanes show alternation; this alternation effect is the basis of all alternation effects occurring in the general behaviour of n-alkanes, dso when other states of matter (liquid state or S,-modification) are involved. The properties of the latter states do not show alternation themselves.Quantitative experimental evidence by means of thermodynamic data has now been obtained. In terms of enthalpy the magnitude of the alternation effect is about 600 cal/mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

1963
1963
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Values for the latter are in fair agreement with those of Schaerer et al, 17,18 but the solid-state transition temperatures are, with the exception of C22H46, below their values. With the exception of c18H38, thermograms from differential thermal analyses showed that upon warming, each compound underwent a solid-state transition P-fa several degrees below its a m.p.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Values for the latter are in fair agreement with those of Schaerer et al, 17,18 but the solid-state transition temperatures are, with the exception of C22H46, below their values. With the exception of c18H38, thermograms from differential thermal analyses showed that upon warming, each compound underwent a solid-state transition P-fa several degrees below its a m.p.…”
supporting
confidence: 86%
“…With the exception of c18H38, thermograms from differential thermal analyses showed that upon warming, each compound underwent a solid-state transition P-fa several degrees below its a m.p. Values for the latter are in fair agreement with those of Schaerer et al, 17,18 but the solid-state transition temperatures are, with the exception of C22H46, below their values. These discrepancies show the presence of impurities.…”
supporting
confidence: 86%
“…The critical temperature (Tc) is determined by the first and the second term of eq 6 U TC = ~J (9) Below this temperature, the first-order phase transition of the chains takes place at Tt where H(T,) is equal to zero. But these temperatures are shifted by the other terms, Gh+i and U.…”
Section: Model and Expression Of The Gibbs Free Energymentioning
confidence: 99%
“…Both experimental and theoretical studies on this phase ® Abstract published in Advance ACS Abstracts, June 1, 1994. 0022-3654/94/2098-6187S04.50/0 transition of n-paraffin chains have been extensively done. [8][9][10][11] Kobayashi calculated the lattice energy in details and succeeded to explain the latent heat at the release of rotational motion of each length of hydrocarbon chains.10 These results are helpful for us to make our calculations on the coagel-gel phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the importance of the n -alkanes (hereafter denoted by C n ), numerous studies have been carried out to determine their thermodynamic properties and their structural behavior. Although numerous values of the temperatures and enthalpies of solid−solid and solid−liquid transitions of C n 's are available ...…”
Section: Introductionmentioning
confidence: 99%